Effect of polyaniline/montmorillonite content on the corrosion protection of epoxy coating. Issue 1 (3rd January 2017) - Zhang, Yingjun; Shao, Yawei; Shi, Qiumei; Wang, Yanqiu; Meng, Guozhe; Li, Ping
Abstract : Purpose: The purpose of this paper was to research the influence of polyaniline/montmorillonite (PANI/OMMT) composite powder content on the corrosion protection of epoxy (EP) coating. Design/methodology/approach: The polyaniline/montmorillonite/epoxy (PANI/OMMT/EP) coatings containing different contents of PANI/OMMT composite powder were prepared on steel. The corrosion protection performances of PANI/OMMT/EP coatings in 3.5 per cent NaCl solutions were investigated by electrochemical impedance spectroscopy. The barrier property of coatings was examined using water absorption analysis. The structure and crosslink density of coatings were examined using scanning electron microscopy and differential scanning calorimetry, respectively. Findings: The PANI/OMMT composite powder could enhance the barrier properties of the EP coating and reduce the corrosion rate of the steel beneath the coating. The coating showed the best corrosion protection performance when 3 per cent PANI/OMMT powder was added to the coating. Originality/value: The research clarified the influence of PANI/OMMT content on the corrosion protection of coating from two aspects: one is the barrier performance of the coating; the other is the corrosion inhibitors for metal substrate.